Severity of self-reported outcomes in patients with cancer in West Java Province, Indonesia - Chandra Isabella Hostanida Purba; Bridget Johnston; Grigorios Kotronoulas (Jurnal Keperawatan Padjadjaran, 2026)
Background: Assessing cancer-related patient-reported outcomes is rare in Indonesia. A prior study identified the need for cancer management at the clinic level to overcome low screening, late diagnosis, late treatment, and awareness of cancer. Purpose: This study aimed to describe cancer patients’ self-reports of the severity of symptoms and how it correlates to their characteristics in West Java Province, Indonesia. Methods: A cross-sectional survey of patients with cancer was conducted. As many as 227 patients (response rate 90.8%) were recruited from RSHS Hospital and nearby shelters using purposive sampling technique. Data were collected via respondent’s characteristics questionnaire and the Integrated Palliative Care Outcomes Scale. Data were analysed using bivariate and multivariate chi square tests. Results: A total of 227 questionnaires were received and analysed (response rate 90.8%). The participants were Sundanese (84%), married (81.5%), 36–55 years old (63.9%), housewives (51.5%), and had primary-level education (57.5%).  These patients had been diagnosed between 6 and 12 months (35.7%), with a mean of 1.69 years (SD 2.7), and most patients were without comorbidities (85%). The mean distance to the hospital was 149.3 km (SD=271.7). The most prominent physical symptom experienced was pain (72.2%), while the most prominent emotional concern was family anxiety (45.4%). More than 50% of participants reported severe symptoms. Further statistics show that there is a correlation between performance and pain scale level with severity of patient-reported outcomes (p-value 0,001;α 0,05). Conclusions: The results suggest that patients reported severe outcomes in physical and psychological. Patients with severe physical showed significantly higher pain levels. Systematic assessment of patient-reported outcomes via inexpensive measures can be a key starting point for the management of patients’ symptoms, especially in countries where palliative care services are less organised. Introducing systematic assessment of reported outcomes tools in local practice can help staff perform assessments with a low budget.  Nurse-led interventions can be implemented to provide holistic care for physical and psychological symptoms.